The Effect of Training on Employees' Performance - Linda Maharani; Ida Nurnida (Jurnal Sekretaris dan Administrasi Bisnis, 2018)
The purpose of this study was to know the effect of training on employees' performance at Pharmacy of PT Kimia Farma Unit Bandung. Method of collecting data was done through distributing questionnaires to 68 respondents. This research applied quantitative and descriptive-causality analysis methods. The samples were taken by probability sampling method with simple random sampling type. Whereas, statistical analysis technique used was simple regression analysis. Analyses of data used were descriptive analysis, classical assumption test, and simple linear regression analysis. The results demonstrated that training significantly influenced by reaching the amount of 41.1% and the rest of 58.9% influenced by other factors which were not examined.